America's Forgotten Terrorists : The Rise and Fall of the Galleanists - Simon, Jeffrey D. (Jeffrey David), 1949- (Book collections on Project MUSE., 2022)
""America's Forgotten Terrorists" tells the story of a movement that nearly anticipated the era that America is currently in and what varying types of terrorism have looked like from the early twentieth century to our current state"--